Development of Hypercrosslinked Hydrophilic Polymer using Dispersion Polymerization Technique for Separation Process - Mohammad Zuhaili, Yahya; Norhayati, Abdullah (Penerbit Universiti Malaysia Pahang, 2016)
Hypercrosslinked microsphere hydrophilic polymer derived from 2-hydroxylethyl methacrylate (HEMA), ethylene glycol dimethacrylate (EDGMA), and vinyl benzene chloride (VBC) have been successfully synthesized using hypercrosslinking reaction chemistry. In this study, dispersion polymerization technique has been used in order to develop precursor prior to hypercrosslinking reaction. Mixture of water/toluene system as a medium polymerization showed promising result with high yield and good quality of microsphere precursor and meanwhile increasing VBC content up to 5% based on monomer feed showed decreasing in quality of microsphere precursor in term of shape and size. FTIR result showed both EDGMA and VBC successfully incorporated into the precursor polymer backbone. After undergo hypercrosslinking reaction, hypercrosslinked microsphere polymer still can retain their original shape as before hypercrosslinking reaction with satisfy quality. From BET analysis, it showed slightly increment in specific surface area of hypercrosslinked microsphere polymer from 10.621 m2/g to 16.831 m2/g.